ANALYSIS OF ONLINE ATTENDANCE POLICY IMPLEMENTATION IN IMPROVING EMPLOYEE DISCIPLINE JNE GUNUNGSITOLI BRANCH OFFICE - Jelita Agung Permata Sari Zendrato; Syah Abadi Mendrofa; Palindungan Lahagu; Sukaaro Waruwu (LPPM YPITI, 2026)
This study analyzes the implementation of online attendance policies to improve employee discipline at the JNE Gunungsitoli Branch Office. Using descriptive qualitative methods through interviews, observations, and documentation, it was found that the online attendance policy was able to improve employee compliance with working hours, attendance transparency, and supervision effectiveness. However, its implementation still faces technical obstacles such as internet network disruptions and application errors, as well as behavioral obstacles such as late attendance and low awareness of discipline among some employees. The positive impact of this policy is seen in increasing discipline and work professionalism, although improvements are still needed. This study recommends improving technological infrastructure, optimizing socialization and training, and consistent supervision with strict sanctions so that the implementation of online attendance can run more optimally.